2008
DOI: 10.1113/expphysiol.2007.041129
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a specific influence of the nitrergic pathway on the peripheral pulse waveform in rabbits

Abstract: The height of the dicrotic notch between the systolic and diastolic peaks of the peripheral pulse wave, expressed as a fraction of the overall amplitude of the wave, is sensitive to nitric oxide (NO) bioactivity. This phenomenon might form the basis of a simple, non-invasive method for determining endothelial function in vivo. We assessed whether the phenomenon is specific to the NO pathway or whether other vasoactive agents have similar effects. The relative height of the dicrotic notch (RHDN) was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…It has subsequently emerged that such drugs exert their vasodilatory effect by being metabolized to NO within the vasculature. Consistent with this, recent studies of the pulse wave in the human finger (Chowienczyk et al, 1999) and the rabbit auricular (central ear) artery (Klemsdal et al, 1994;Nier et al, 2008;Weinberg et al, 2001) have shown that alteration of the NO pathway also changes the relative height of the dicrotic notch. Substances that stimulate NO production (e.g.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…It has subsequently emerged that such drugs exert their vasodilatory effect by being metabolized to NO within the vasculature. Consistent with this, recent studies of the pulse wave in the human finger (Chowienczyk et al, 1999) and the rabbit auricular (central ear) artery (Klemsdal et al, 1994;Nier et al, 2008;Weinberg et al, 2001) have shown that alteration of the NO pathway also changes the relative height of the dicrotic notch. Substances that stimulate NO production (e.g.…”
Section: Introductionmentioning
confidence: 59%
“…L-NAME, type II diabetes, hypercholesterolaemia) increase notch height. Vasoactive drugs unrelated to the NO pathway do not appear to have such effects (Morikawa, 1967;Nier et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since the a/b is a function of arterial wave reflection, the lesser increase of the a/b with SNP compared with pG z can be interpreted as follows: 1) the major site of action of SNP was on large-conduit vessels and pG z on smaller resistance vessels; or 2) pG z also stimulated release of prostacyclin, which provided significant additional vasodilatation to cause the lengthening of the time of wave reflection (4). Nier et al (42) showed, in rabbits, that the relative height of the dicrotic notch was dose dependently decreased by the cyclooxygenase Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is attributed to vasodilatation of the resistance vessels, thereby lengthening the arterial pulse wave reflection time (26). In humans, descent of the dicrotic notch of digital and aortic pulse waves has been observed with nitrate and albuterol administration, as well as with exercise (10,26,29,39,42,46). This finding is mediated through the action of NO, since inhibition of NO synthesis with N G -nitro-L-arginine methyl ester (L-NAME) or N G -monomethyl-L-arginine prevents descent of the dicrotic notch after acetylcholine or albuterol administration in rabbits and humans, respectively (26, 52).…”
mentioning
confidence: 99%